EKSPERIMENTASI PEMBELAJARAN MATEMATIKA DENGAN MODEL KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) YANG DIMODIFIKASI PADA MATERI PERSAMAAN GARIS LURUS DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP NEGERI DI KABUPATEN PONOROGO - Suharyanto, Suharyanto; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2013)
Abstract: This research aimed to know: (1) which of the NHT modified model, the NHT model or the direct learning model promoted the students? better achievement on mathematics, (2) which one is better, the students with visual learning style, auditorial learning style, or kinesthetics learning style, and (3) in various learning style, which one having better achievement on mathematic, the NHT modified model, the NHT model or the direct learning model. This research was a quasi-experiments research with factorial design 3x3. The population of this research was the eight grade students of State Junior High Schools in Ponorogo. The sample was taken by the use of stratified cluster random sampling technique. The data collecting made use the documentation, questionnaire, and test methods. The documentation method was used to collect the data of the second-semester students? achievement on mathematics in the academic year 2011/2012 as found in their report books. This finding was further applied to check the balance of the students of the two exsperiment classrooms and one control classroom. The questionnaire was used to find the type of learning style mostly owned by the students. Whiles, the test was used to determine the students? achievement on mathematics in the straight line equation topic. Examination of hypothesis used an unbalanced two way analysis of variances at significance levels 5%. The results of the research was as follows: (1) the students? achievement on mathematics due to NHT modified model was equally due to NHT model, while the two models above was better than due to direct learning model, (2) there was no distinction among visual learning style, auditorial learning style, and kinesthetics learning style based on the students? achievement on mathematics, and (3) in various of learning style, the students? achievement on mathematics due to NHT?s modification model was equally due to NHT model, while the two models above was better than due to direct learning model.Keywords: the NHT Modified, the Direct Learning Model, the Learning Style